Effect of Early Patient Contact on the Empathy of Medical Students in Qom, Iran - Soleiman Ahmadi; Mojdeh Vaezzadeh; Narges Alizadeh; Mohammad Aghaali; Amin Habibi (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum, 2023)
Background and Objectives: Empathy is one of the most important concepts in patient care. This study aims to design and implement an early patient contact program and investigate its effect on the empathy of medical students in Qom, Iran. Methods: This is a case-control interventional study. Sixty-four students from Qom University of Medical Sciences were recruited by a convenience sampling method and were randomly divided into intervention and control groups. The instrument was the Jefferson Scale of Empathy. First, empathy training was provided to the both groups. Then, the intervention group participated at three sessions of attending hospital. The collected data were entered into SPSS software, verion 22 and analyzed by chi-square test and paired t-test. Results: There was no significant difference between the two groups before the intervention. After the intervention, the empathy score was 74.04±10.32 in the intervention group and 68.31±8.14 in the control group; the difference between the groups was statistically significant. Conclusion: Early patient contact before the start of the internship period increases the empathy of medical students.